Abrasive notches along the Atlantic Patagonian coast and their potential use as sea level markers: the case of Puerto Deseado (Santa Cruz, Argentina). Issue 11 (2nd July 2014) - Bini, M.; Isola, I.; Pappalardo, M.; Ribolini, A.; Favalli, M.; Ragaini, L.; Zanchetta, G.
ABSTRACT Patagonia Argentina is a key area for the study of sea level changes in the southern hemisphere, but the availability of reliable sea level markers in this area is still problematic. In fact the storm deposits (beach ridge) commonly used here to reconstruct past sea level oscillations introduce a wide error. Along the Puerto Deseado coast (Santa Cruz), morphometric analyses of 11 features were carried out using traditional measurement tools and a digital software‐based method (tested on one selected feature) with the aim to investigate the possibility of their use as sea level markers. By undertaking accurate topographic profiles we identified the relationship between notches and current sea level. In detail, we identified two clusters of notch retreat point elevations, with a very low internal variability. The lower was located a little below the mean high tide level (mHT) and the upper located at least 0.5 m above the maximum high tide level (MHT). Field observations of tidal levels and the position of notches suggest that the lower notches are active and the upper are inactive. This study on the abrasive notches attests their quality as sea level markers and opens up the use of fossil abrasive notches as palaeo sea level markers because the error linked to these features is substantially smaller than that introduced by beach ridges commonly used in the study area. Copyright © 2014 John Wiley & Sons, Ltd.